Of Short Story (Journal of Teaching and Research in English Literature, 2012)
Literature represents the enthusiasm and apathy, hope and despair, thrill of joy and state of pain in the history of any nation. In fact, literature is not of one age but all ages, not of one country but all countries. Literature consists of many genres. Each age has its own particular line of interest and its own particular way of thinking and feeling. The environment, the body and the atmosphere are necessary for the creation of any work of art besides the heart and soul. In that way, the short story as a special genre has got utmost name and fame among the readers of literature, generally of any time particularly present lovers of literature. A short story is one that is not too unorganized, but a narrative in style. It is a work of prose fiction, and most of the terms for analyzing the components parts, the types and the various narrative techniques of the novel are applicable to the short story also. This paper tries to throw light upon some of the aspects of short stories as enunciated by the experts, literati, and researchers of short stories.